Metodologi Tafsir Al-Tahrir Wa Al-Tanwir Karya Muhammad Tahir Ibnu ‘Asyur - Khaerul Asfar (AL-AQWAM: Jurnal Studi Al-Quran dan Tafsir, 2022)
This study aims to elaborate the specific methodology of al-Tah{ri>r wa al-Tanwi>r interpretation by Muh}ammad T{a>hir Ibnu ‘A<syu>r, an expert of interpretation a Maliki-based has written his interpretive work using the analytical method (tah}li>li>) with a linguistic pattern (lughawi>) and tried to criticize his previous works. In terms of methodology, Ibnu ‘A<syu>r interpretation uses an analytical method (tah}li>li>), with the pattern used is language (lughawi>). The data collection technique used in this study as a whole is a literature research or book survey. Data is processed using qualitative methods, namely processing data based on the values contained in each data. The results showed that there is a distinctiveness that other interpretations do not have, namely the tendency of interpretation to the pattern of language (lughawi>). This is evidenced by (1) Writing down points that have not existed in the previous interpretation, (2) Explaining each i’jaz of the Qur’an in detail and contained in a separate book, (3) Revealing arabic linguistic values (balaghah, nahwu, sharaf, mantik), (3) Revealing the style of language (badi’) contained in a sentence of the Qur’an clearly by explaining the ways of its use (4) Explaining the harmony of one verse with another.